Anti-cancer green bionanomaterials: present status and future prospects. Issue 4 (2nd October 2017) - Barabadi, Hamed; Ovais, Muhammad; Shinwari, Zabta Khan; Saravanan, Muthupandian
ABSTRACT: Cancer is one of the most common health problems responsible for outnumbered deaths worldwide. Nanomedicine plays an important role in developing alternative and more effective treatment strategies for cancer theranostics. However, the toxicity, high cost and nanoparticles (NPs) production complexity are some of the major issues that obstruct the use of existing nanomedicine. Recently, the green synthesis of biogenic NPs from plants and microbial sources has become an emerging field due to their safer, eco-friendly, simple, fast, energy efficient, low-cost and less toxic nature. Interestingly, NPs play a key role in diagnosis of tumor at the initial stage by allowing cellular visualization. Furthermore, prospective applications of green NPs include magnetically responsive drug delivery, anti-cancer activity, photo-thermal therapy and bio-imaging. The present review provides perspective on the use of anti-cancer green bionanomaterials with a focus on their present status and future prospects in the theranostics of cancer. GRAPHICAL ABSTRACT: